Toksisitas merkuri sebagai faktor risiko epilepsi anak - Sri Sutarni (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Mercury (Hg) is one of the heavy metal which uses to make silver handicraft. Kotagede in special regency of Yogyakarta is one of the place to product that. The side effect of mercury consists of a few aspects of neurological deficits as epilepsy. The aim of this paper: want to know the risk factors of mercury to epilepsy in children with Hg exposure. Methods: by case control design to be taken the children from integrity health care Semoyan, Kotagede. As control group the children of integrity health care Pondok Suruh, Cangkringan. Result: 45 children consist of 21 (46,67%) with epilepsy from WHO diagnose. Thirtheen male (28,89%) and 8 female (17,78%) samples compare with control group. The most common age was 1-5 years ofd: 14 children (31,11%) pregnant fess from 9 months: 9 children (20%), birth of body weight = 2,5 kg: 11 children (24,44%). Twelve children (26,67%) was born by doctors. Incomplete immunization of 12 children (26,67%), water for drink were wheel of 11 children (24,22%) and parents as silvers handicraft of 16 children (35,56%).By univariate analysis the Odds Ratio of each variable which significant correlation to epilepsy: irregular control of pregnancy (OR = 11,667; 95% C.i 2,373 — 57,365 p = 0,01) pregnancy < 9 months (OR 27,353; 95% C.i 3,320 —225, 365; p = 0,00). incomplete immunization (OR = 7,00; 95% C.i 1,993 — 24.581; p = 0,01), the parents as silver handicraft (OR = 11,88; 95% C.i 2,442 — 38,267, p 0,00).By multivariate analysis: immunization and the parents workers were significant to be epilepsy. Conclusions: Hg exposure could influence to child neurological aspects as epilepsy. Vaccination and the parent's workers as silver handicrafts must be careful for prevention of child epilepsy. Suggestions: Complete vaccination to the children less than 5 years old especially for silver handicraft workers and environment of Hg exposure. To protect environment and people who lived with Hg exposure. Keywords: mercury, epilepsy, children, exposure